Role of suprabasin, a new biomarker in squamous cell carcinoma and basal cell carcinoma - Ucer, Ozlem; Kocaman, Nevin (Churchill Livingstone, 2022)
Introduction: Suprabasin is a newly discovered protein linked to various human diseases including cancer. It may does have an effect on the development and expression of some non-melanoma skin cancers such as basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). BCC is the most common non-melanoma skin cancers worldwide, while SCC comes as the second in terms of prevalence. In certain cases, it is very important to distinguish between these two carcinomas from each other and from normal skin samples. This study was aimed at investigating the characteristics of suprabasin expression in squamous cell carcinoma and basal cell carcinoma and whether it can be used as a biomarker.Materials and methods: Thirty control, ninety SCC and thirty BCC cases obtained from the archives of the Department of Pathology, Faculty of Medicine, Firat University, were examined by immunohistochemical staining for suprabasin.Results: Increased suprabasin expression was observed in tumour tissues and normal skin samples in SCC. As the grade increased in SCC, suprabasin expression decreased. No suprabasin expression was observed in the lesion area in BCC.Conclusion: Suprabasin can be reported as a biomarker for SCC and used to differentiate SCC from BCC. Expression of suprabasin in SCC can be used to determine grade. Absence of suprabasin expression in BCC can be used for differential diagnosis
Keywords: Squamous cell carcinoma; Basal cell carcinoma; Suprabasin; Immunohistochemistry